The Expansion and Spatial Pattern of Shopping and Tourism Services Facilities in North Bandung Region, Indonesia - Lia Warlina; Lusia Elsa Dika Damayanty (Indonesian Journal of Science and Technology, 2021)
This study aims to identify the expansion and spatial patterns of shopping and tourism services facilities and evaluate whether the locations are aligned with the spatial plan map of the North Bandung region. The research was conducted by taking inventory of shopping and tourism services facilities in 2010, 2012, 2014, 2016, and 2018. The locations were plotted into maps to calculate each point's spatial pattern for each period using the nearest neighbor analysis method. The 2018 map was overlaid with a spatial plan map to identify whether the existing location aligns with the regional plan. The first results were the expansion and spatial pattern maps of shopping North Bandung area for 2010, 2012, 2014, 2016, and 2018; that show the broadest expansion of shopping facility in 2018 with a clustered pattern. The second results were expansion, and spatial pattern maps of tourism service facilities in the same period show that since 2014 the expansion started with clustered patterns. The evaluation results show that only convenience stores were located in protected areas, but all tourist service facilities were located in these locations. This finding is essential for local governments in monitoring spatial use.